Ethylene ethyl phosphate as a multifunctional electrolyte additive for lithium-ion batteries. Issue 23 (13th March 2015) - Gao, D.; Xu, J. B.; Lin, M.; Xu, Q.; Ma, C. F.; Xiang, H. F.
<x xml:space="preserve">Abstract</x> The effects of ethylene ethyl phosphate (EEP) as a multifunctional electrolyte additive on safety characteristics and electrochemical performance of lithium-ion batteries are investigated.